Evidence for Intramyocardial Disruption of Lipid Metabolism and Increased Myocardial Ketone Utilization in Advanced Human Heart Failure. Issue 8 (23rd February 2016) - Bedi, Kenneth C.; Snyder, Nathaniel W.; Brandimarto, Jeffrey; Aziz, Moez; Mesaros, Clementina; Worth, Andrew J.; Wang, Linda L.; Javaheri, Ali; Blair, Ian A.; Margulies, Kenneth B.; Rame, J. Eduardo
Abstract : Background—: The failing human heart is characterized by metabolic abnormalities, but these defects remains incompletely understood. In animal models of heart failure there is a switch from a predominance of fatty acid utilization to the more oxygen-sparing carbohydrate metabolism. Recent studies have reported decreases in myocardial lipid content, but the inclusion of diabetic and nondiabetic patients obscures the distinction of adaptations to metabolic derangements from adaptations to heart failure per se. Methods and Results—: We performed both unbiased and targeted myocardial lipid surveys using liquid chromatography-mass spectroscopy in nondiabetic, lean, predominantly nonischemic, advanced heart failure patients at the time of heart transplantation or left ventricular assist device implantation. We identified significantly decreased concentrations of the majority of myocardial lipid intermediates, including long-chain acylcarnitines, the primary subset of energetic lipid substrate for mitochondrial fatty acid oxidation. We report for the first time significantly reduced levels of intermediate and anaplerotic acyl-coenzyme A (CoA) species incorporated into the Krebs cycle, whereas the myocardial concentration of acetyl-CoA was significantly increased in end-stage heart failure. In contrast, we observed an increased abundance of ketogenic β-hydroxybutyryl-CoA, in association with increased myocardial utilization of β-hydroxybutyrate. We observed a significant increase in the expression of the gene encoding succinyl-CoA:3-oxoacid-CoA transferase, the rate-limiting enzyme for myocardial oxidation of β-hydroxybutyrate and acetoacetate. Conclusions—: These findings indicate increased ketone utilization in the severely failing human heart independent of diabetes mellitus, and they support the role of ketone bodies as an alternative fuel and myocardial ketone oxidation as a key metabolic adaptation in the failing human heart. Abstract : Supplemental Digital Content is available in the text.